Combination of the endoscopic septonasal flap technique and bioabsorbable steroid-eluting stents for repair of congenital choanal atresia in neonates and infants: a retrospective study - Peng-peng Wang; Li-xing Tang; Jie Zhang; Xiao-jian Yang; Wei Zhang; Yang Han; Xiao Xiao; Xin Ni; Wen-tong Ge (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Multiple surgical approaches have been proposed to repair the congenital choanal atresia. However, there remains no general consensus about the optimal surgical technique. This study aimed to describe and evaluate outcomes of the endoscopic septonasal flap technique combined with bioabsorbable steroid-eluting stents for repair of congenital choanal atresia in neonates and infants. Methods Clinical data of 37 neonates and infants with congenital choanal atresia who received nasal endoscopic surgery with the flap technique between January 2018 and July 2020 were analyzed retrospectively. All patients underwent the ultra‑low‑dose paranasal sinus computed tomography imaging preoperatively to confirm diagnosis and plan the surgery. In these patients, the mirrored L-shaped flap technique was performed for bilateral atresia and the cross-over L-shaped flap technique was performed for unilateral atresia. A total of 22 patients had silicone stents postoperatively and 15 patients had bioabsorbable steroid-eluting stents postoperatively. Silicone stents were removed at one month postoperatively under secondary general anesthesia, while no anesthesia was needed to remove the bioabsorbable steroid-eluting stents. Postoperative follow-up ranged from 10 months to 3 years. Results The septonasal flap technique was performed in all patients. Compared with the silicone stents group, the average operative duration and the hospital length of stay in the bioabsorbable steroid-eluting stents group were decreased [(97.46 ± 15.37) min vs (83.49 ± 19.16) min t = 13.733, P < 0.001] [(12.8 ± 3.22) d vs (7.67 ± 3.91) d t = 15.082, P < 0.001], the average number of procedures was reduced [(2.04 ± 0.64) vs (1.00 ± 0.001), t = 82.689, P < 0.001], the differences were statistically significant. There were no reports of postoperative restenosis and complications in the bioabsorbable steroid-eluting stents group, and follow-up endoscopic examinations showed patency and stable nasal passages in all cases. Conclusions The endoscopic septonasal flap technique can effectively expose and expand the choanal bony structure for repair of congenital choanal atresia in neonates and infants. The combined use of this technique along with bioabsorbable steroid-eluting stents can help prevent the need for revision procedures and also against stent-related injuries.